De novo synthesis of budding yeast DNA polymerase alpha and POL1 transcription at the G1/S boundary are not required for entrance into S phase. - Falconi, M M (1993)
The POL1 gene, encoding DNA polymerase alpha (pol alpha) in Saccharomyces cerevisiae, is transiently transcribed during the cell cycle at the G1/S phase boundary. Here we show that yeast pol alpha is present at every stage of the cell cycle, and its level only slightly increases following the peak of POL1 transcription. POL1 mRNA synthesis driven by a GAL1 promoter can be completely abolished without affecting the growth rate of logarithmically growing yeast cultures for several cell divisions, although the amount of the pol alpha polypeptide drops below the physiological level. Moreover, alpha-factor-arrested cells can enter S phase and divide synchronously even if POL1 transcription is abolished. These results indicate that the level of yeast pol alpha is not rate limiting and de novo synthesis of the enzyme is not required for entrance into S phase.